Factors Influencing Financial Distress in Jakarta Islamic Index (JII) Companies Listed on the Indonesia Stock Exchange, 2014-2019 - Jumaili, Salman; Agryadini, Roselika; Afrizal, Afrizal (Jurnal Cakrawala Akuntansi, 2023)
This study was conducted to determine the effect of price earning ratio, inventory turn over (ITO), audit committee size, frequency of audit committee meetings, inflation, and exchange rates on financial distress in Jakarta Islamic Index (JII) companies listed on the Indonesia Stock Exchange. 2014-2019 period. The independent variables used in this study are price earning ratio, inventory turn over (ITO), audit committee size, frequency of audit committee meetings, inflation, and exchange rates. The dependent variable in this study is financial distress. This type of research is quantitative research. The population in this study is the Jakarta Islamic Index (JII) companies listed on the Indonesia Stock Exchange for the 2014-2019 period. The sample in this study was taken using purposive sampling method with a total sample of 11 companies. The data analysis used in this study is multiple linear regression analysis with the help of the SPSS program. The data in this study are secondary data obtained from the official website of IDX. The results of this study indicate that the frequency of audit committee meetings has a significant negative effect on financial distress, and the price earnings ratio has a significant positive effect on financial distress. Meanwhile, inventory turnover, audit committee size, inflation and exchange rate have no significant effect on financial distress